2015
DOI: 10.1242/jcs.169896
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila retinoblastoma protein, Rbf1, induces a debcl and drp1-dependent mitochondrial apoptosis.

Abstract: In accordance with its tumor suppressor role, the retinoblastoma protein pRb can ensure pro-apoptotic functions. Rbf1, the Drosophila homolog of Rb, also displays a pro-apoptotic activity in proliferative cells. We have previously shown that the Rbf1 pro-apoptotic activity depends on its ability to decrease the level of anti-apoptotic proteins such as the Bcl-2 family protein Buffy. Buffy often acts in an opposite manner to Debcl, the other Drosophila Bcl-2-family protein. Both proteins can localize at the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 66 publications
5
37
0
3
Order By: Relevance
“…We have previously shown that the JNK pathway activation induced by rbf1 involved reactive oxygen species (ROS) in dying cells. 28 Many data report an activation of the JNK pathway depending on ROS. For example, in mammalian cells, the JNKKK ASK1 has been extensively characterized as a ROS-responsive kinase.…”
Section: Signals For Example the C-terminal Regions Of Slpr And Dtak1mentioning
confidence: 99%
“…We have previously shown that the JNK pathway activation induced by rbf1 involved reactive oxygen species (ROS) in dying cells. 28 Many data report an activation of the JNK pathway depending on ROS. For example, in mammalian cells, the JNKKK ASK1 has been extensively characterized as a ROS-responsive kinase.…”
Section: Signals For Example the C-terminal Regions Of Slpr And Dtak1mentioning
confidence: 99%
“…Altogether these observations show that that the survival of a cell is regulated by the interplay between RHG pro-apoptotic genes and the mitochondrial fusion machinery. Why mitochondrial localization of RHG pro-apoptotic proteins is significant for caspase activation, and what is the role of mitochondrial fragmentation and permeabilization remains unknown (Clavier, Ruby et al 2015, Clavier, Rincheval-Arnold et al 2016). …”
Section: Mechanisms Of Apoptosismentioning
confidence: 99%
“…En effet, Debcl et Buffy modulent la réponse apoptotique embryonnaire provoquée par irradiation [19]. Par ailleurs, Debcl joue un rôle crucial dans l'apoptose induite par Rbf1 alors que Buffy s'y oppose [17,21]. Ainsi, chez la drosophile, bien que le rôle des protéines de la famille Bcl-2 dans le contrôle de la mort cellulaire développementale apparaisse mineur, ces protéines semblent jouer un rôle majeur dans l'apoptose induite par un stress ou par l'homologue, chez la drosophile, de la protéine oncosuppressive pRb.…”
Section: Mort Cellulaireunclassified
“…Chez la drosophile, un lien existe entre les membres de la famille Bcl-2, la dynamique mitochondriale et la mort cellulaire. Nous avons récemment montré que Debcl et Drp1 pouvaient interagir entre eux et que Buffy inhibait cette interaction (Figure 2) [21]. De façon intéressante, Debcl module la localisation mitochondriale de Drp1 au cours de l'apoptose et l'apoptose induite par Debcl, nécessite Drp1 et implique une fragmentation mitochondriale.…”
Section: Mort Cellulaireunclassified
See 1 more Smart Citation